2020
DOI: 10.1182/blood-2020-136148
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of High Risk (HR) Smoldering Multiple Myeloma (SMM) with Carfilzomib, Lenalidomide, and Dexamethasone (KRd) Followed By Lenalidomide Maintenance (-R): A Phase 2 Clinical and Correlative Study

Abstract: Background: HR-SMM is a plasma cell disorder with a 5-year risk of progression to symptomatic multiple myeloma (MM) of ~75% without therapy. Early treatment with novel therapies, may decrease the risk of progression and prolong survival as evidenced by studies (Quiredex and ECOG E3A06) comparing lenalidomide ± dexamethasone to observation. Randomized studies in MM have demonstrated that triplet are superior to doublet regimens and whole exome sequencing in HR-SMM suggests a more treatment-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A subsequent phase II study in high-risk SMM (Mayo Clinic or PETHEMA models) assessed KRd (8 cycles) + lenalidomide maintenance (KRd-R). 86 After a median potential follow-up of 27.3 months, the overall response rate was 100% and 78% of patients achieved a best response of stringent complete remission. The primary objective of MRD-negative complete remission was achieved by 70.2%, with a median duration of 5.5 years.…”
Section: Treatment Options With Novel Agentsmentioning
confidence: 96%
“…A subsequent phase II study in high-risk SMM (Mayo Clinic or PETHEMA models) assessed KRd (8 cycles) + lenalidomide maintenance (KRd-R). 86 After a median potential follow-up of 27.3 months, the overall response rate was 100% and 78% of patients achieved a best response of stringent complete remission. The primary objective of MRD-negative complete remission was achieved by 70.2%, with a median duration of 5.5 years.…”
Section: Treatment Options With Novel Agentsmentioning
confidence: 96%
“…Carfilzomib, lenalidomide, and dexa meth a sone (KRD)-based earlyinter ven tion approaches with reported pre lim i nary data have shown deep responses; the GEMCESAR trial reported a postconsolidation min i mal resid ual dis ease neg a tive (MRD-) rate of 57%, and a nontransplant approach showed an MRDcomplete response (CR) rate of 70%. 45,47 Although these responses are prom is ing, the util ity of an MRD end point and impact of acute and longterm toxicities of inten sive ther apy remain to be seen.…”
Section: Table 2 (Continued)mentioning
confidence: 99%
“…No deaths were reported. Grade 3-4 treatment-related AE occurred in 33% of patients and included cytopenias, thromboembolism, skin rash and lung infections [52].…”
Section: Proteasome Inhibitor-based Treatments For Smoldering Myelomamentioning
confidence: 99%